Book Review. Andrew J. Owen, Desire After Dark: Contemporary Queer Cultures and Occultly Marvelous Media - Wolff, Richard (Journal for religion, film and media, 2022)
Book review of Andrew J. Owen's Desire After Dark on supernatural beings as vampires or witches, who challenge heteronormative perspectives on gender and society.